(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
For more than 40 years, low calcium alkali-activated cement composite, or in other words, geopolymer, has been around. In recent years there has been increased interest in this material and its properties. It is mainly due to the claim that geopolymer is the cement of the future. This claim is based on environmental factors. For instance, the CO2 emissions for geopolymer binder can be up to 6 less than for Portland cement binder. Most of the researches regarding geopolymer composite properties examine only mechanical and long-term properties in compression. There has been a lack of long-term tests in tension due to difficulties in performing them. As the tensile stresses are an essential part of structure assessment, it is necessary to evaluate new material properties as thoroughly as possible. Due to the nature of geopolymer specimen hardening (polymerisation), there is a difference in modulus of elasticity development and shrinkage caused by binding that could have factors that regular Portland cement specimens do not.This article aims to evaluate the surface composition of plain and 1% PVA reinforced geopolymer compact tension specimens that have been subjected to creep and shrinkage tests. Specimen cross-section images were acquired using the scanning electron microscope (SEM). Using the quantitative image analysis method, amounts of cross-section composition elements are determined. Furthermore, the amount of cracks is determined and compared between plain and PVA fiber-reinforced specimens.It has been determined that even though 1% of PVA fibre-reinforced specimens have lower tensile strength, their creep and shrinkage strains are lower, and the number of microcracks at the notch base of the specimen. Still, it has to be acknowledged that the amount of air voids in all analysed specimens is relatively high.